EXTH-62. PRECLINICAL EFFICACY OF THE IMIPRIDONE ONC-206 AGAINST MEDULLOBLASTOMA. (9th November 2020) - MacDonald, Tobey; Malhotra, Anshu; Liu, Jingbo; Zhang, Hongying; Schneiderjan, Matthew; Vega, Jose Velazquez; Prabhu, Varun; Allen, Joshua
Abstract: Treatment for medulloblastoma (MB) is typically ineffective for MYC amplified or metastatic SHH, Group 3 and 4 subgroups. Promising preclinical and clinical results have been obtained for adult and pediatric malignant glioma treated with ONC-201, a selective antagonist of DRD2, a G-protein coupled receptor that regulates prosurvival pathways. Herein, we report the activity of ONC-201 and ONC-206, which has increased non-competitive antagonism of DRD2, against MB. We treated three different MB cell types representative of SHH- and Group 3-like cells, with varied levels of DRD2 expression, and consistently observed increased cell death in a dose-dependent manner at lower doses of ONC-206 compared to ONC-201. We also evaluated ClpP as an additional drug target in MB. ClpP is a mitochondrial protease that has been shown to directly bind and be activated by ONC 201, and is highly expressed at the protein level across pediatric MB, malignant glioma and ATRT, but not normal brain. We observed that similar to ONC-201, ONC-206 treatment of MB cells induces the restoration of mitochondrial membrane potential to the non-proliferative state, degradation of the mitochondrial substrate SDHB, reduction in survivin and elevation in ATF4 (integrated stress response). Importantly, ONC-206 treatment induced significant cell death of patient-derived SHH, WNT, and Group 3 tumors ex vivo and Group 4 cells in vitro, while having no observable toxicity in normal brain. ONC-206 treatment of a transgenic mouse model of Shh MB in vivo significantly reduces tumor growth and doubles survival time in a dose-dependent manner following 2 weeks of therapy. Additional in vivo data will be reported in preparation for a planned Phase I study of ONC-206 in children with malignant brain tumors.